Evaluation on senior high school English textbooks - Yosyie Azharia Winimurti; Dedi Rahman Nur (Universitas Sarjanawiyata Tamansiswa, 2019)
In Indonesia, English teachers use textbooks to help students in the teaching-learning process and use it as a self-help resource to get rich input in learning. To improve the quality of English language teaching in Indonesia, this research was conducted to measure whether the three books used in Senior High School, i.e. â€œBahasa Inggrisâ€, â€œPathway to Englishâ€, and â€œOutcomes Upper Intermediateâ€ are right or not. This research used Alan Cunningsworthâ€™s theory on excellent textbook and tried to find the strengths and weaknesses of the three books based on the given methods above. The study was conducted using evaluation research to evaluate the three English textbooks used by some schools in Yogyakarta. Evaluation steps included taking some samples from the books to see whether they meet the criteria of good textbooks that the researcher developed based on Cunningsworthâ€™s framework. The research found out that Bahasa Inggris meets five standards: aims and approaches, design and organisation, topic, teachersâ€™ book, and political consideration. Pathway to English meets four standards of excellent textbook by Cunningsworth: aims and approaches, design and organisation, teachersâ€™ book, and political attention. Outcomes Upper Intermediate matches five principles of excellent manual by Cunningsworth: goals and methods, design and organisation, skills, topic, and teachersâ€™ book. The researcher also found out that the strengths and weaknesses of â€œBahasa Inggrisâ€, â€œPathway to Englishâ€, and â€œOutcomes Upper Intermediateâ€. From the findings above, the researcher suggests the teacher use three textbooks in the teaching-learning process because three books meet the criteria in a good book.